Thucydides' The Peloponnesian War: Causes, Pretexts and Realist Traditions - Boucoyannis, Deborah A. (Études helléniques / Hellenic Studies, 1998)
The following article explores the appropriation of Thucydides by the Realists, especially in terms of justice and morality. The analysis suggests that the discernment of “true causes” requires careful examination and cannot be based on pronouncements by actors, of which Thucydides himself was one. His account, read carefully, pushes one to think more deeply about the relation of appearances to “what actually happened”, and not just to what was, or was not, said.